Facility development for a combined cancer therapy - Fadeev, A.M.; Ivanov, S.M.; Perelstein, E.A.; Polozov, S.M.; Tkachev, S.I. (Вопросы атомной науки и техники, 2012)
The system for local hyperthermia of cancers was simulated. This system is based on independently phased dipoles with frequency 150 MHz. The electromagnetic field distributions are calculated in cut of tissue-equivalent phantom. It was shown that the electromagnetic field can be focused in desirable volume by means of independent vary of amplitude and phase of each dipole. The advantages of combined therapy are discussed for common using of hyperthermia with chemotherapy, radiation therapy or surgery. Проведено моделирование работы системы для локальной гипертермии онкологических заболеваний на основе системы независимо фазируемых дипольных излучателей, работающих на частоте 150 МГц. Получены картины распределения электрических полей в сечении облучаемого образца (тканеэквивалентного фантома). Показана возможность фокусировки электромагнитного поля в необходимом объеме за счет независимого изменения фазы и амплитуды излучения каждого из диполей. Рассмотрены перспективы комбинированного использования гипертермии и химической или лучевой терапии и хирургии. Проведено моделювання роботи системи для локальної гіпертермії онкологічних захворювань на основі системи незалежно фазіруємих дипольних випромінювачів, що працюють на частоті 150 МГц. Отримано картини розподілу електричних полів у перерізі опромінюваного зразка (тканееквівалентного фантома). Показана можливість фокусування електромагнітного поля в необхідному об’ємі за рахунок незалежної зміни фази і амплітуди випромінювання кожного з диполів. Розглянуто перспективи комбінованого використання гіпертермії та хімічної або променевої терапії та хірургії.